2007
DOI: 10.1021/ma0704818
|View full text |Cite
|
Sign up to set email alerts
|

Triphase Equilibria in Cellulose Nanocrystal Suspensions Containing Neutral and Charged Macromolecules

Abstract: The effect of added nonadsorbing macromolecules on the phase behavior of suspensions of electrostatically stabilized cellulose nanocrystals is examined. Triphasic isotropic−isotropic−nematic equilibria develop in cellulose nanocrystal suspensions to which a mixture of dextran and blue dextran is added. Phase diagrams for different combinations of uncharged dextran and anionically charged blue dextran are presented. The range of dextran concentrations at which the triphase equilibrium is produced is strongly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 49 publications
1
37
0
1
Order By: Relevance
“…It is already well known that solutions of CNCs in water can form a gel phase in the presence of ions [12][14]. In this study we demonstrated that the electrodissolution of a metallic electrode controlled the growth of such a gel phase.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…It is already well known that solutions of CNCs in water can form a gel phase in the presence of ions [12][14]. In this study we demonstrated that the electrodissolution of a metallic electrode controlled the growth of such a gel phase.…”
Section: Discussionsupporting
confidence: 58%
“…At high CNCs concentration around 10wt% the liquid crystalline phase dominates and the suspension turns to a gel. Increasing the ionic strength of a CNCs suspension can also result in phase separation into isotropic and gel phase [12][14]. In this context, aqueous suspensions of carboxylated CNCs (cCNCs) displayed birefringence patterns but did not flocculate or sediment owing to the polyanionic character imparted by the negative charges on the cCNCs surface [15].…”
Section: Introductionmentioning
confidence: 99%
“…These results are complementary to the findings of Lekkerkerker and coworkers who mainly studied the effect of non‐adsorbed polymer chains on the phase change of different colloidal particles such as platelets or rods . This effect was also studied by Beck‐Candenado et al using CNC suspensions . They could obtain a transition from two phases (isotropic and nematic) to three phases (two isotropic and one nematic) when adding more Blue Dextran in a 8.7 g/g CNC suspension.…”
Section: Resultsmentioning
confidence: 99%
“…In this phase separation, blue dextran was partitioned preferentially into the upper isotropic phase; however, the lower dextran-poor chiral nematic phase exhibited a rather distorted fingerprint texture with numerous disclinations. Further investigation of these lines demonstrated that the "isotropic-isotropic-chiral nematic" phase equilibrium developed when an undyed neutral dextran was added along with the anionically charged blue dextran to a biphasic CNC suspension (e.g., 8.7 wt%) [95]. The concentrations of the two dextrans needed to produce the three-phase equilibrium were strongly influenced by their molecular weights and overall charge density.…”
Section: Phase Separation Behavior Of Cnc/water Suspensionsmentioning
confidence: 99%